2023
DOI: 10.3390/coatings13010211
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Detectors Based on Halide Perovskite Materials

Abstract: Halide perovskite has remarkable optoelectronic properties, such as high atomic number, large carrier mobility-lifetime product, high X-ray attenuation coefficient, and simple and low-cost synthesis process, and has gradually developed into the next-generation X-ray detection materials. Halide perovskite-based X-ray detectors can improve the sensitivity and reduce the detectable X-ray dose, which is applied in imaging, nondestructive industrial inspection, security screening, and scientific research. In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In contrast, the ALS method can successfully develop dense, highly crystalline perovskite films with low defects. 108 For example, W. Qian and research team demonstrated the application of the ALS method to facilitate the growth of s uniform CsPbI 2 Br-based perovskite film for radiation detection and they showed that the thickness and grain size of the film were enhanced steadily with an increment in the growth time. 109 Fig.…”
Section: Active Layer Fabrication Techniquesmentioning
confidence: 99%
“…In contrast, the ALS method can successfully develop dense, highly crystalline perovskite films with low defects. 108 For example, W. Qian and research team demonstrated the application of the ALS method to facilitate the growth of s uniform CsPbI 2 Br-based perovskite film for radiation detection and they showed that the thickness and grain size of the film were enhanced steadily with an increment in the growth time. 109 Fig.…”
Section: Active Layer Fabrication Techniquesmentioning
confidence: 99%
“…Halide perovskite has remarkable optoelectronic properties, such as high atomic number, large carrier mobility-lifetime product, high X-ray attenuation coefficient, and simple and lowcost synthesis process, and has gradually developed into a next-generation X-ray detection material. In the work by Tan et al, the fabrication methods of halide perovskite film and the development progress of halide-perovskite-based X-ray detectors were introduced [8].…”
mentioning
confidence: 99%